Wearable microfluidic sweat pH sensor - Kuruvinashetti, Kirankumar; Vajhadin , Fereshteh; Jalali, Pezhman; Rosenegger, David; Sanati Nezhad , Amir; Komeili, Amin (CMBES Proceedings, 2023)
Skin interfaced wearable devices consisting of microfluidic channels, electrochemical and calorimetric assays utilize the sweat as analyte and therefore offer noninvasive and real time physiological information . The biomarkers present in the sweat could be effectively used for comprehending various disorders such as diabetes, cystic fibrosis, and stress as well as monitoring of drugs, pH, and electrolytes. Major challenges of most of these microfluidic wearable technologies are related to 1) the contamination of old and new sweats, 2) stability of biosensing methods, and 3) variation of sweat pH during the sensing of biomarkers. Cortisol is the principal biomarker present in the sweat which is directly correlated to stress. Hence real time monitoring of stress could be achieved by measuring the cortisol in the sweat. The real time or longitudinal measurement of stress in diseases like concussion is much needed as stress in these patients can lead to significant health issues and as well as it can be life threatening to them. One technical challenge of accurate detection of cortisol using biosensors is the dependency of the sensors to pH of solution. Therefore, it is crucial to measure pattern concentration of cortisol. Here we developed simple, low-cost wearable microfluidic chip that measures the sweat pH in real time. This sensor can be easily integrated with cortisol sensors embedded within microfluidic chips.